2014
DOI: 10.1002/bjs.9451
|View full text |Cite
|
Sign up to set email alerts
|

Lymph node size as a predictor of lymphatic staging in colonic cancer

Abstract: The contribution of lymph nodes smaller than 3 mm to nodal staging is limited. Increased node size is associated with increased nodal yield, and could be a confounder in the relationship between prognosis and nodal harvest in patients with N0 disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…Changes in the mechanical properties and associated alterations in macrostructure, such as size, and microstructure, including the distribution of collagen fiber diameter and alignment as well as glycosaminoglycan content, may reflect the effects of disease (21, 4347). Enlarged LNs are a prominent clinical manifestation in numerous types of cancers (39, 40, 48), and a correlation between LN stiffening and LN metastasis in a small cohort of patients with lung cancer has been described (49). Matrix remodeling, including deposition and cross‐linking, is characteristic of tumors (21) and lymphedema (50, 51).…”
Section: Discussionmentioning
confidence: 99%
“…Changes in the mechanical properties and associated alterations in macrostructure, such as size, and microstructure, including the distribution of collagen fiber diameter and alignment as well as glycosaminoglycan content, may reflect the effects of disease (21, 4347). Enlarged LNs are a prominent clinical manifestation in numerous types of cancers (39, 40, 48), and a correlation between LN stiffening and LN metastasis in a small cohort of patients with lung cancer has been described (49). Matrix remodeling, including deposition and cross‐linking, is characteristic of tumors (21) and lymphedema (50, 51).…”
Section: Discussionmentioning
confidence: 99%
“…This confirms previous findings in Stage II–III colon cancer but there is currently no explanation for this phenomenon. One possibility is that a stronger host anti‐tumor immune response results in larger regional LNs that are detected more easily . Another suggestion is that individual variation in the number of mesenteric LNs may reflect variations in immune competence.…”
Section: Discussionmentioning
confidence: 99%
“…The results of a recently completed study by our group also revealed associations between the number of intratumoral T-lymphocytes and LN5 status, lymph node yield, and outcome (submitted for publication). Immune response was also described as a confounder of the prognostic relevance of lymph node count in another study [27]. Relationships of CCs with lymph node morphology, immune , f).…”
Section: Discussionmentioning
confidence: 98%